Monitoring of an orphaned Bosnian Mountain Horse foal: A one-year case study (VETERINARIA, 2025)
This case report describes a foal of the Bosnian MountainHorse (Equus ferus caballus) type, found in a cachectic andlife-threatening condition in Eastern Bosnia, in April 2024. Thefoal, approximately two months old and orphaned, was adoptedby local residents. It was fed a diet based on diluted cow’smilk, forage and concentrates, supplemented with minerals andvitamins. The foal was monitored until it reached one year ofage. Morphometric measurements included front cannon girth,thorax girth, body length, height at withers, and height at croup.Despite non-standard feeding and care conditions, the foalshowed progressive recovery and development comparable tohealthy foals of the same breed.
Keywords: Bosnian mountain horse; orphan foal; morphometry